Extremophilic Exopolysaccharides: Biotechnologies and Wastewater Remediation - Banerjee, Aparna; Sarkar, Shrabana; Govil, Tanvi; González-Faune, Patricio; Cabrera-Barjas, Gustavo; Bandopadhyay, Rajib; Salem, David R.; Sani, Rajesh K. (Frontiers in Microbiology, 2021)
Various microorganisms thrive under extreme environments like hot springs, hydrothermal vents, deep marine ecosystems, hyperacid lakes, acid mine drainage, high UV exposure and more. To survive against the deleterious effect of these extreme circumstances, they form a network of biofilm where exopolysaccharides (EPSs) comprise a substantial part. The EPSs are often polyanionic due to different functional groups in their structural backbone, including uronic acids, sulphated units, and phosphate groups. Altogether, these chemical groups provide EPSs with a negative charge allowing them to (a) act as ligands towards dissolved cations as well as trace and toxic metals, (b) be tolerant to the presence of salts, surfactants and alpha-hydroxyl acids, and (c) interface the solubilisation of hydrocarbons. Owing to their unique structural and functional characteristics, EPSs are anticipated to be utilized industrially for the remediation of metals, crude oil, and hydrocarbons from contaminated wastewaters, mines, and oil spills. The biotechnological advantages of extremophilic EPSs are more diverse than traditional biopolymers. The present review aims at discussing the mechanisms and strategies for using EPSs from extremophiles in environment bioremediation. Additionally, the potential of EPSs as fascinating biomaterials to mediate biogenic nanoparticles synthesis and treat multicomponent water contaminants is discussed.